SINTOMAS DEPRESSIVOS E NÍVEL DE ATIVIDADE FÍSICA EM DISCENTES DA UNIVERSIDADE DO OESTE DE SANTA CATARINA (UNOESC) EM XANXERÊ - Neves, Kauana; Ledur Antes, Danielle (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
Introduction: It is essential to understand that mental health and physical health are two intertwined and interdependent elements of life, and like many physical illnesses, mental and behavioral disorders result from a complex interaction of biological, psychological and social factors. Goal: To analyze the association between depressive symptoms, socioeconomic conditions, health and lifestyle habits in students at the Western University of Santa Catarina – UNOESC, campus Xanxerê. Method:To evaluate, a computerized questionnaire will be applied on a day of academic class, containing questions from the IPAQ and also on medical diagnosis of depressive disorder. Students enrolled in any undergraduate course at UNOESC Xanxerê will be accepted, the data will be later tabulated and categorized into specific software to verify normality and then analyzes of the relationship between the variables will be performed, according to the most appropriate test. Results:The work is still under construction. Conclusion: It is expected that among students with a good level of physical activity and a healthier lifestyle, they have fewer diagnoses of depression.